Earl Browder the failure of American Communism - Ryan, James G. (Univ. of Alabama Press, 1997)
In this new biography James Ryan shows Browder as a man of many contradictions. He was shy but sought publicity. He prided himself on being a Stalinist, yet viewed himself as a loyal American. He moved up within the structure of the organization (the CPUSA or CP) by anticipating changes in the party line, but believed he could assert his individuality without recrimination